Essence of Self-Education Competence in Pedagogy - Striguna, Santa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Promoting the challenges of future education system in the context of public education, the term of competence and self-education competence is set in the spotlight of the article. Analyzing the comprehension of the essence of the diverse competence, the author systematizes the qualities which characterize the competence. The term of self-education and its structure based on the analysis of theoretical resources is characterized, the criteria are conveyed which characterize the future teachers’ self-education process. The goal of the article: on the basis of the theoretical resource studies systematize the diverse comprehension of the concept competence and characterize the structure and components of the students, future teachers’ self-education competence.